1999
DOI: 10.1200/jco.1999.17.11.3476
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Development of Children After a Cerebellar Tumor in Infancy: A Longitudinal Study

Abstract: PURPOSE: To assess the long-term neuropsychologic effects experienced by children who have tumors in the cerebellum that are diagnosed and treated during infancy. PATIENTS AND METHODS: Twenty-seven children with posterior fossa tumors diagnosed at less than 36 months of age were assessed prospectively with a comprehensive set of age-appropriate tests. Group means and SDs are reported for assessments conducted at diagnosis (analysis 1) and at the most recent follow-up appointment (analysis 2). Cognitive develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 50 publications
8
92
0
5
Order By: Relevance
“…Indeed, some studies have found that survivors have more cognitive and educational deficits than their siblings. [5][6][7][8][9] Other studies have found no differences between survivors of childhood cancer and their healthy siblings in behavioral, educational and social problems, as well as feelings of distress, guilt and psychosomatic symptoms. [10][11][12][13] In contrast, in an early study, siblings of childhood cancer survivors showed more distress than the survivors in perceived social isolation; 11 or survivors performed like their siblings in psychological adjustment but did significantly worse than their siblings in educational outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have found that survivors have more cognitive and educational deficits than their siblings. [5][6][7][8][9] Other studies have found no differences between survivors of childhood cancer and their healthy siblings in behavioral, educational and social problems, as well as feelings of distress, guilt and psychosomatic symptoms. [10][11][12][13] In contrast, in an early study, siblings of childhood cancer survivors showed more distress than the survivors in perceived social isolation; 11 or survivors performed like their siblings in psychological adjustment but did significantly worse than their siblings in educational outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…4 A progressive decline in intellectual functioning after irradiation of larger brain volumes has been well-established. [7][8][9] Academic competence has received less research attention despite being a measure of applied cognitive functioning in a child's natural setting. While IQ and academic performance are correlated in typically developing children, a dissociation in these abilities has been found in certain clinical populations, [10][11][12][13] including cancer survivors.…”
Section: Journal Of Clinical Oncology O R I G I N a L R E P O R T V Omentioning
confidence: 99%
“…Especially for tumors of the CNS, the localization, and for other cancer groups the age at diagnosis, lengths of stay in the hospital and total duration of therapy, as well as cranial irradiation, are most likely of major inÂŻuence. Copeland et al (20) concluded that children with cerebellar tumors and non-irradiation therapy in early infancy have only minimal declines in neurocognitive development compared with patients treated with cranial radiotherapy. Further, this group emphasized the possible late effects of intrathecal chemotherapy (21).…”
Section: Discussionmentioning
confidence: 99%